Memory - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
Memory is about measurement. It begins at 0 and 1 and ends at the size of the memory. Other units of memory include number of bits [1] in a single unit of memory and memory size at a certain level (encapsulation [2] and abstraction [3]). The last measurement is memory size at all levels.